A continuous approximation method for dynamic pricing problem under costly price modifications. (October 2017) - Dasci, Abdullah; Huang, Rongbing
Abstract: This paper presents a heuristic method to solve a dynamic pricing problem under costly price modifications. This is an extremely difficult nonlinear problem that has been solved only for a few special instances. Here we provide a new approach that involves an approximate reformulation of the problem, which can subsequently be solved in closed-form using elementary calculus techniques. Numerical results show that the approach is quite accurate; approximating the optimal revenue with errors usually much less than 1%. Moreover, the accuracy rapidly improves as the optimal number of price changes increases, which are precisely the cases conventional approaches would fail. Abstract : Highlights: We present a heuristic method to solve a dynamic pricing problem under costly price modification. Our approach can handle the most general version of the problem to date. Our approach can be used to develop asimple but highly effective heuristic method to find the precise number and times of price changesand prices to charge. Our results suggest that the number of price changes is extremely robust to the changes in fixed cost but relatively more sensitive to the demand parameters.